Analysis of work performance appraisal organizational commitment and work discipline on employee performance through compensation to Work Units-National Narcotics Agency North Sumatra - Deasy Merry Natalina; Muhammad Chaerul Rizky (International Journal of Management, Economic and Accounting, 2024)
This study aims to test and analyze the effect of work performance appraisal, organizational commitment and work discipline on employee performance through compensation to work units-national Narcotics Agency North Sumatra. The research method used is a quantitative method. Data analysis techniques using SMART PLS. The population in this study is all employees of the National Narcotics Agency of North Sumatra Province which amounted to 126 people and with the slovin formula a sample of 56 employees was obtained. The results of the study show that organizational commitment and work discipline have a positive and significant effect on compensation. Organizational commitment and work discipline have a positive and significant effect on employee performance. As well as organizational commitment and work discipline have a positive and significant effect on employee performance through compensation